A comparison of quadriceps electromyographic activity with the position of the foot during the parallel squat - Boyden, G.; Kingman, J.; Dyson, R. (The Journal of Strength and Conditioning Research, 2000)
Six experienced lifters performed 3 squats in each of 4 foot positions: 10° inward, 0°, 10° outward, and 20° outward. These were performed at 2 weight conditions: 65 and 75% of 1 repetition maximum. Surface electromyographic activity of the vastus medialis, vastus lateralis, and rectus femoris on the right leg was analyzed in terms of the activity duration and peak levels of activity. Results and analysis of variance indicated that the foot rotation position did not influence the mean peak activity or mean duration of activity of vastus medialis, vastus lateralis, or rectus femoris. The practice of adopting foot rotation to selectively strengthen individual muscles of the quadriceps group was not supported by this study, which involved smaller, more readily adopted, and comfortable levels of foot rotation than did those previously investigated.